(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Ayurveda is a scientific text which covers all aspects of Rachana Sharir and Kriya Sharir. This Sharir is now-a-days modernized as Anatomy and Physiology. To understand anatomy the primary knowledge of anatomical landmarks is essential. Reference points located by visual inspection, palpation, or computer assistance are useful in localizing structures on or within the human body are called Anatomical landmarks. These are frequently used by Anatomists and clinicians to guide both diagnosis and treatment. In Ayurveda, the concept of Anatomical landmark is already present but in scattered manner. The concept of Nabhi in Ayurveda is many folded concept which needs more exploration. It can be considered as Koshthanga, as Marma, as Sira & Dhamani Prabhava Sthana, as an anatomical landmark and many more. In this paper an attempt has been made to collect references related to Nabhi from various Samhitas indicating it as an anatomical landmark and by analyzing these references logically, the concept of Nabhi as an important landmark has been established and reconstructed in accordance with modern Anatomical landmark categories.